Aquaporin-4 and MOG autoantibody discovery in idiopathic transverse myelitis epidemiology. (23rd July 2019) - Sechi, Elia; Shosha, Eslam; Williams, Jonathan P.; Pittock, Sean J.; Weinshenker, Brian G.; Keegan, B. Mark; Zalewski, Nicholas L.; Lopez-Chiriboga, Alfonso Sebastian; Jitprapaikulsan, Jiraporn; Flanagan, Eoin P.
Abstract : Objective: Diagnostic criteria from 2002 classify transverse myelitis (TM) as idiopathic or disease associated but predate the discovery of aquaporin-4 (AQP4)–immunoglobulin G (IgG) and myelin oligodendrocyte glycoprotein (MOG)-IgG, which associate with TM. Prior incidence estimates of idiopathic TM (ITM) range from 1 to 6.2 per 1 million. We sought to determine whether the population-based incidence and prevalence of ITM were reduced by testing patients with ITM for AQP4/MOG-IgG and reclassifying seropositive cases as having disease-associated TM. Methods: For this observational study, we retrospectively identified all cases of incident (January 1, 2003–December 31, 2016) and prevalent (December 31, 2016) ITM in Olmsted County (85% white) by using the Rochester Epidemiology Project medical records linkage system. ITM was defined by the 2002 Transverse MyelitisConsortium Working Group diagnostic criteria. Available sera were tested for AQP4-IgG and MOG-IgG. Results: Twenty-four patients (incident 22, prevalent 17) initially met 2002 ITM criteria (longitudinally extensive TM [LETM] 6). Sera were tested for AQP4-IgG in 22 of 24 (92%) and MOG-IgG in 21 of 24 (88%). Three seropositive cases (AQP4-IgG 2, MOG-IgG 1) were identified and reclassified as having disease-associated TM, accounting for 14% of total incident and 12% of total prevalent cases. AQP4-IgG and MOG-IgG seropositive cases represented 50% (3 of 6) of idiopathic LETM. After reclassification of seropositive patients, the final ITM incidence was 8.6 per 1, 000, 000 and prevalence was 7.9 per 100, 000. Three cases of ITM (14%) subsequently fulfilled multiple sclerosis criteria within the study period. Conclusions: The availability of AQP4-IgG and MOG-IgG modestly reduced ITM incidence and prevalence, which remained higher than previously reported in this predominantly white population. Incorporation of these biomarkers into future revisions of TM diagnostic criteria should be considered.